Adaptation to Climate Change at Local Scale: A CFD Study in Porto Urban Area (2017)
Green infrastructures play an essential role in urban planning, namely with their potential to reduce the impact from air pollution episodes together with extreme weather events. This chapter focuses on the assessment of green infrastructures’ benefits on current and future microclimate and air quality patterns in Porto’s urban area (Portugal). The effects of green infrastructures on flow dynamics are evaluated for the baseline scenarios by means of numerical and physical simulations, using the computational fluid dynamics (CFD) model VADIS and the wind tunnel of the University of Aveiro. The baseline morphological (BM) scenario focuses on the current morphological characteristics of Porto’s urban area, while a baseline green (BG) scenario comprises the replacement of built-up areas by green areas and parks. In addition, the benefits of green infrastructures on air quality are assessed for the baseline and under future climate scenarios. The air quality simulations focus on particulate matter, one of the most critical air pollutants with severe impacts on human health. For the BM scenario, the simulated concentrations are compared with hourly averaged PM10 concentrations measured during a weekday at the air quality station located within the study domain.